2021
DOI: 10.1111/ipd.12886
|View full text |Cite
|
Sign up to set email alerts
|

Differences in specific concerns perceived by parents of children with cleft lip and/or palate based on the types of cleft

Abstract: With a worldwide prevalence of approximately 9.92 per 10,000 newborn births, 1 cleft lip and/or cleft palate (CL/P), which includes cleft lip only (CL), cleft lip and palate (CLP), and cleft palate only (CP), is one of the most common congenital orofacial anomalies in humans. 2 Japan reports the highest prevalence worldwide (20.4 per 10,000 births). 1 Children with CL/P experience effects on their speech, hearing, appearance, and cognition that can lead to long-lasting adverse outcomes for their health and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The scientific literature has reported that the greater the orofacial dysfunction, the greater the impairment of the quality of life of individuals with orofacial clefts. 26,27 Of the limitations found in this study, the response system adopted can be considered. This may have resulted in the ceiling and floor effects, however, it opens up the possibility of future studies to confirm or refute this hypothesis.…”
Section: Scale (B-lsojcleft-s) the Social Stigma Related To The Prese...mentioning
confidence: 99%
“…The scientific literature has reported that the greater the orofacial dysfunction, the greater the impairment of the quality of life of individuals with orofacial clefts. 26,27 Of the limitations found in this study, the response system adopted can be considered. This may have resulted in the ceiling and floor effects, however, it opens up the possibility of future studies to confirm or refute this hypothesis.…”
Section: Scale (B-lsojcleft-s) the Social Stigma Related To The Prese...mentioning
confidence: 99%